Estimação das perdas produtivas em frangos de corte devido ao estresse por calor - Santos, João Paulo Aquino (2014)
The environmental control of sheds for the broiler chickens production can bring better performance results with the reduction of production losses due to heat, and the variations in climatic events may significantly alter the viability of the production system. The objective of this study was to estimate the production loss due to heat in the broiler production system. This research was carried out through a meta- analysis in which 52 related research were used to heat stress in broiler chickens aged 1-42 days old. The data were processed according to the method of meta- analysis and explored by data mining technique for obtaining decision models to assist in the determination and quantification of production losses in broilers. The results demonstrate that the climatic variables the wet bulb temperature and dry bulb temperature in Celsius degrees and the Temperature- Humidity Index (THI ) is possible to estimate the performance loss of broilers influencing low weight gains and worst feed conversions ratio, with values of 32° C dry bulb temperature, relative humidity above 40 % , wet bulb temperature above 25.51 or 25.77º C and 23.29º C of THI as threshold conditions to potential production losses at 30.99% to feed conversion, 36.54% to weight gain and 52.04% to daily weight gain.